Molecular Dynamics Simulation of the Nano- scale Solutal Marangoni Convection - Yosuke Imai; Takuya Yamamoto; Yasunori Okano; Ryuma Sato; Yashuteru Shigeta (ASEAN Journal of Chemical Engineering, 2017)
Non-equilibrium molecular dynamics simulations for the 2- and 3-phase systems were performed to investigate the flow with two free surfaces in a nanoscale, where solute, water, and argon were assigned as each phase. We observed that the behaviors of some 3-phase systems significantly differ from those of 2-phase systems. In all 2- phase systems, the solutes just diffused into the water phase. On the other hand, the solutes were transferred along the liquid-gas interfaces in the case of 3-phase systems with a large surface tension gradient. These results indicated that solutal Marangoni convection existed even in the nano-scale and it affected mass transfer greatly.